2013
DOI: 10.1007/978-3-642-41199-1_16
|View full text |Cite
|
Sign up to set email alerts
|

Arrestins in Apoptosis

Abstract: Programmed cell death (apoptosis) is a coordinated set of events eventually leading to the massive activation of specialized proteases (caspases) that cleave numerous substrates, orchestrating fairly uniform biochemical changes than culminate in cellular suicide. Apoptosis can be triggered by a variety of stimuli, from external signals or growth factor withdrawal to intracellular conditions, such as DNA damage or ER stress. Arrestins regulate many signaling cascades involved in life-or-death decisions in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 224 publications
(320 reference statements)
2
10
0
Order By: Relevance
“…The strong pro-apoptotic effect of GSK-3 inhibitors in extrinsic pathways triggered by death receptors has been well documented in our study and previous studies in other cancer cell types [34]. Selective knockdown of glycogen synthase kinase-3β but not glycogen synthase kinase-3α by RNA interference enhances TRAIL-induced cell death in pancreatic cancer cells [35].…”
Section: Discussionsupporting
confidence: 78%
“…The strong pro-apoptotic effect of GSK-3 inhibitors in extrinsic pathways triggered by death receptors has been well documented in our study and previous studies in other cancer cell types [34]. Selective knockdown of glycogen synthase kinase-3β but not glycogen synthase kinase-3α by RNA interference enhances TRAIL-induced cell death in pancreatic cancer cells [35].…”
Section: Discussionsupporting
confidence: 78%
“…Kook et al (27) used mouse embryonic fibroblasts (MEFs) cells whereas the current study adopted HepG2 cells. β-arrestin has been demonstrated to have diverse roles via distinct mechanisms in various experimental models (22). In the present study, overexpression of β-arrestin2 using GFP-Arrb2 plasmids demonstrated that β-arrestin2 exerted anti-apoptotic role in HepG2 cells.…”
Section: Discussionsupporting
confidence: 54%
“…Recent studies have demonstrated that β-arrestins contribute to anti-apoptotic effects in apoptosis that is induced by a variety of stimuli (5,8,22). However, the role of β-arrestins in TRAIL-induced apoptosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There are some indications that βArrs may trigger malignant signalling and cancer progression through activation of protein kinases (Src, MAPKs, PI3K), growth factor receptors, and transcription factors 5 , 7 , 13 . Furthermore, βArrs affect cell survival and can prevent GPCR-induced apoptosis 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…These are significant modulators of cellular growth and cancer cell migration, invasion, and metastasis [9][10][11][12] .There are some indications that βArrs may trigger malignant signalling and cancer progression through activation of protein kinases (Src, MAPKs, PI3K), growth factor receptors, and transcription factors 5,7,13 . Furthermore, βArrs affect cell survival and can prevent GPCR-induced apoptosis 14,15 .On the other hand, some studies indicate that βArr-mediated signalling reduces cell proliferation, migration, invasion, and metastasis, and induces apoptosis and an anti-cancer response pattern in some types of cancer [16][17][18] . They can facilitate cell death by mediating apoptotic signalling 17,18 .…”
mentioning
confidence: 99%